Power management of an electric motorcycle using Battery State Controller (BSC) - Rabiatuladawiah Abu Hanafiah (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
As technology progresses, the investigations on the motorcycle developed into an even more complex model as it needs to be able to include the dynamics of the motorcycle at high speed. The controller in the electrified vehicle application requires it to manage and monitor the battery state and several other functions related to the battery in the system. In this research, a controller or the Battery State Controller (BSC) system, is designed to assist the driver by managing the speed of the electric motorcycle in stages to avoid drastic speed changes during low battery capacity condition. A realistic model of the electric motorcycle with both kinematics and dynamics is developed as the fundamental model for the design of the BSC system. Additionally, a Fuzzy-based speed control strategy is employed in the design of the BSC system for power management in the electric motorcycle. To optimised the power management strategy in an electric motorcycle, the BSC is deployed in the developed electric motorcycle model in the simulation platform before the performance is verified in an experimental study. The BSC controller is also designed to be robust in managing the power of electric motorcycle with the application of various driving profiles as the input speed such as the WMTC(urban), WLTC(low) and UDDS. The simulations reveal that less speed with a minimum of 20% speed reduction and a better distance coverage of minimum 2.7% range increases at the battery cut-off operation with the implementation of the BSC system on various road profiles. The results from test bench implementation confirm the ability of the developed BSC system for optimized power management with a minimum of 1% speed reduction and a minimum 4.3% range increases. Additionally, the measurement uncertainty analysis is also performed to investigate the confidence level of the measured readings. The test bench is recorded to perform at only 7% of error and a standard deviation of 1.89 km/h. Thus, the experimental test conducted confirms the ability of the developed BSC system for efficient power management of electric motorcycles in a real-time environment.